PRE-SERVICE ENGLISH TEACHERS’ ACCEPTANCE OF TECHNOLOGY INTEGRATION IN EFL REMOTE LEARNING (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
In EFL Remote learning, the use of technology integration in EFL learning during the transition period since pandemic Covid-19 has a significant impact on the teaching and learning process. In a teaching environment, this is essential. The term ICT integration in education refers to the use of computer-based information technology in daily classroom activities. The study evaluates the Preservice English Teachers' experience in using technology integration during teaching internships at EFL remote learning. 10 Pre-service English teachers are selected as the participant of this research. The descriptive qualitative method covers Pre-service English teachers' experiences in using technology integration at EFL remote learning. The instruments used to collect data are questionnaires and interviews. This study is expected to overview pre-service teachers' newteaching experience at EFL remote learning.